FEATURES OF THE COURSE OF PREGNANCY IN DICHORIONIC DIAMNIOTIC TWINS IN COMPARISON WITH SINGLETON PREGNANCY (Global Conference on Medical and Health Sciences, 2026)
The incidence of twin pregnancies has increased worldwide due to the widespread use of assisted reproductive technologies and delayed childbearing. Although dichorionic diamniotic (DCDA) twin pregnancy is considered the most favorable type of twin gestation, it remains associated with an elevated risk of obstetric and perinatal complications.To evaluate the clinical and anamnestic characteristics and pregnancy course in women with DCDA twin pregnancies and compare them with those of women with singleton pregnancies.
Keywords: Dichorionic diamniotic twins, twin pregnancy, singleton pregnancy, clinical characteristics, obstetric outcomes, perinatal outcomes, risk factors.